Contextual and Attitudinal Determinants of Attitudes towards Immigrants: Security Implications - Petrović, Boban (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
Immigration issues and relations with immigrants have been updated in recent years due to a large number of immigrants from the Middle East and Africa on the road to European Union countries. The attitudes of citizens of Serbia and other countries in Europe towards immigrants range from acceptance to extremely negative attitudes and violent behavior towards them. Such a situation indicates that the issue of Serbian citizens' attitudes towards immigrants is important from the standpoint of safety. Therefore, this study has focused on determinants of attitudes of Serbian citizens towards immigrants. Determinants of the contextual level, primarily economic security and life in a multiethnic environment, as well as from the individual: social dominance orientation, right-wing authoritarianism, nationalism, and religiosity, were investigated. The research was conducted on a sample of 540 respondents from the general Serbian population, and data were collected online. The results showed that economic security has no direct effect on a prosocial attitude towards immigrants, while a multi-ethnic environment, contrary to expectations, has a negative effect. In line with previous research, attitudinal dimensions also have a negative effect, especially social dominance orientation, but also nationalism and religiosity. It is especially important to emphasize that two significant interactions are detected. They show that, in contrast to individuals who are neither religious nor nationalistic, those who are more religious and with more pronounced nationalistic attitudes express negative attitudes towards immigrants if they originate from multiethnic backgrounds. These findings are consistent with the cultural threat hypothesis.